Association Between CYP2C9 and CYP2C19 Genetic Polymorphisms and Antiseizure Medication-Induced Adverse Reactions Among Peruvian Patients with Epilepsy - Alvarado, Angel T. (2025)
Background/Objectives: Epilepsy is characterized by recurrent, unprovoked, self-limiting seizures of genetic, acquired, or unknown origin. It affects more than 50 million people worldwide. The prevalence in Peru is 11.9–32.1 per 1000 people. Our objective was to describe the association between CYP2C9 and CYP2C19 genetic polymorphisms and adverse reactions induced by antiseizure medications among Peruvian patients with epilepsy. Methods: A descriptive observational study was conducted on Peruvian patients with epilepsy. Non-probability, non-randomized, purposive sampling was carried out through consecutive inclusion. Genomic DNA was obtained from venous blood samples. Genotypes were determined by real-time PCR using specific TaqMan probes to identify the alleles of interest. Results: In total, 89 Peruvian patients with epilepsy were recruited at the Alberto Sabogal Sologuren National Hospital-ESSALUD: 45 were male (23.6 ± 10.0 years) and 44 were female (24.0 ± 12.4 years). The observed frequencies for CYP2C9*2, CYP2C9*3, CYP2C19*2, CYP2C19*3, and CYP2C19*17 were 0.034 (T allele), 0.034 (C allele), 0.14 (A allele), 0.00 (A allele), and 0.03 (T allele), respectively. Patients with intermediate and poor metabolic phenotypes of CYP2C9 and CYP2C19 had a significantly higher risk of adverse drug reactions (ADRs) (OR = 3.75; 95%CI: 1.32–10.69; p = 0.013), compared with normal metabolizers. Polytherapy was a predictor increasing the likelihood of ADRs (OR = 4.33; 95% CI: 1.46–12.80; p = 0.008). Conclusions: In this cohort of Peruvian patients with epilepsy, the reduced-function alleles CYP2C9*2, CYP2C9*3, and CYP2C19*2, associated with decreased metabolic activity, were significantly linked to an increased risk of adverse drug reactions induced by antiseizure medications. Polytherapy further heightened this risk. Collectively, these findings highlight the clinical relevance of CYP2C9 and CYP2C19 genotyping to enhance the safety of antiseizure pharmacotherapy in Latin American settings, where pharmacogenomic evidence remains limited.